Variável lingüística: conceituação, problemas de descrição gramátical e implicações para a construção de uma teoria gramatical - Oliveira, Marco Antônio de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
In this paper I examine the concept of linguistic variable. Variants of a linguistic variable are determined in terms of sameness of context and meaning. It is argued here that controlling the context is not an easy task, and that we must (1) extend the notion of context beyond structural context, and (2) explore the structural context to the last detail so to  avoid labelling as variation an alternation between X and Y that can be predicated from the grammar. Concerning meaning, it is argued here that it is not always possible for one to be sure whether two (or more) linguistic forms say the same thing, mainly when it comes to syntactical phenomena. Finally, a few hypotheses are proposed, from the observation of the evolution of some linguistic variables, as to the relationship between system and variation.